GPE 2020 Country-level Prospective Evaluations: First annual Report Kenya - Rawal, Prepared Shenila; Aslam, Monazza; Outhred, Rachel (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:XN28CFK6
Keywords: ⛔ No DOI found

Measuring the Information Society Report 2018 – Volume 2: Country Profile_Senegal - International Telecommunications Union (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:2BP8IRAP

National Education Sector Strategic Plan - Ministry of Education, Kenya (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:MH6HTIBF

Third Medium Term Plan 2018-2022 - The National Treasury and Planning (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:FG8UXQP8

Kenya National Examination Council (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:LVGWP5NJ

M-Shule - Together we learn, together we succeed - M-Schule LTd (2018)
M-Shule is the first adaptive, mobile learning management platform designed to improve performance for millions of primary school students across Kenya and Sub-Saharan Africa
Library Catalog: m-shule.com KerkoCite.ItemAlsoKnownAs: 2405685:SBPUP4HV

National Education Sector Strategic Plan v2 - Ministry of Education, Kenya (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:K364JWL8

Human Development Indices and Indicators: 2018 Statistical Update: Senegal - UNDP (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:ENN9MWVG

IDA Project Paper on a Proposed Additional Credit to the Republic of Senegal for a Quality Improvement and Equity of Basic Education Project - World Bank (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:Z7Y4HEQH

Baseline-Endline Report: Reaching the Unreached (RtU) through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan - Ferreira, Frances; Cruz, Charisse; Smith, Kristina; Commonwealth of Learning (COL) (British Columbia) (Commonwealth of Learning, 2018)
This report documents the baseline-endline study by the GIRLS Inspire team's Reaching the Unreached project to examine the implications of skills training and education for women's and girls' empowerment and sustainable livelihoods in Bangladesh, India and Pakistan. It is based on data collected from quarterly reports mirrored against the project outcomes, meeting reports and surveys from March 2016 to March 2017. The quarterly and meeting reports documented the activities undertaken to provide training for unreached women and girls in the selected countries. While the actual training was offered exclusively to women and girls, the reports and surveys also captured the input of men and boys in terms of their participation in various community events and as staff members of the partner organisations.
KerkoCite.ItemAlsoKnownAs: 2339240:6XL37978 2405685:NM8GPWDQ
Keywords: Access to Education; Bangladesh; Barriers; Child Abuse; Decision Making; Distance Education; Dropouts; Economic Factors; Educational Attainment; Elementary Secondary Education; Employer Attitudes; Employment; Empowerment; Females; Foreign Countries; Health; Income; India; Job Skills; Marriage; Occupational Aspiration; Pakistan; Postsecondary Education; Program Effectiveness; Skill Development; Sustainability; Training; Womens Education

UIS Statistics - UNESCO Institute for Statistics (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:D63GEHHY 2405685:IZ8998MR 2405685:WTPRBCKB
Keywords: ___working_potential_duplicate

UIS Statistics - UNESCO Institute for Statistics (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:D63GEHHY 2405685:IZ8998MR 2405685:WTPRBCKB
Keywords: ___working_potential_duplicate

Majorities in sub-Saharan Africa own mobile phones, but smartphone adoption is modest - Silver, L; Johnson, C (Pew Research Center's Global Attitudes Project, 2018)
Large majorities in all six sub-Saharan countries surveyed own mobile phones. Ownership is highest in South Africa, where about nine-in-ten adults own a
Library Catalog: www.pewresearch.org Section: Publications EdTechHub.ItemAlsoKnownAs: 2405685:HK8TBZ3W

GSMA Mobile Connectivity Index | Sierra Leone - GSMA (2018)
The GSMA Mobile Connectivity Index is a global mobile connectivity and digital economy guide covering 150 countries and 7 sub-regions
Library Catalog: www.mobileconnectivityindex.com EdTechHub.ItemAlsoKnownAs: 2405685:AGNKXIPC

Investigating the Relationship between Students' Digital Literacy and Their Attitude towards Using ICT - Jan, Salma (International Journal of Educational Technology, 2018)
This study aimed to explore the relationship between secondary school students' digital literacy and their attitude towards using information and communication technology in a private secondary school in Karachi, Pakistan. For this study, the data were collected through survey questionnaire using google forms. The total sample size for this study was 344 secondary school students having almost equal ratio of male and female. On bivariate correlation analysis, digital literacy was found to be associated with students' attitude towards using information and communication technology (ICT) and other ICT related demographics. Further analysis using multiple linear regression analysis showed that digital literacy (DL), use of the tablet and smartphone, prior training in the use of computer and frequency of computer use significantly affect students' attitude towards using ICT.
Publisher: International Society for Educational Technology KerkoCite.ItemAlsoKnownAs: 2339240:GN89MJ8X 2405685:YJQ7SI9N
Keywords: Computer Literacy; Educational Technology; Foreign Countries; Handheld Devices; Incidence; Secondary School Students; Student Attitudes; Student Characteristics; Technological Literacy; Technology Uses in Education; Telecommunications; Training; ⛔ No DOI found

Ghana Multiple Indicator Cluster Survery 2017/2018 - Ghana Statistical Survey & UNICEF (2018)
The Multiple Indicator Cluster Survey Six (MICS 6) was conducted in 2017/18 by Ghana Statistical Service in collaboration with the Ministry of Health, Ministry of Education, Ministry of Sanitation and Water Resources, Ministry of Gender, Children and Social Protection, Ghana Health Service and the Ghana Education Service as part of the Global MICS Programme. Technical support was provided by the United Nations Children’s Fund (UNICEF), with government funding and financial support of UNICEF, KOICA, UNDP, USAID and the World Bank through the Statistics for Results Facility – Catalytic Fund (SRF-CF). The Global MICS Programme was developed by UNICEF in the 1990s as an international multi-purpose household survey programme to support countries in collecting internationally comparable data on a wide range of indicators on the situation of children and women. MICS surveys measure key indicators that allow countries to generate data for use in policies, programmes, and national development plans, and to monitor progress towards the Sustainable Development Goals (SDGs) and other internationally agreed upon commitments.
KerkoCite.ItemAlsoKnownAs: 2339240:SGN2Z4NH 2339240:TA8SP5N7 2405685:65AVJUKD 2405685:65LG7X5H 2405685:JV6UZAGF

The status of early childhood education in Pakistan: Inside stories - Khan, Afzal (Contemporary Issues in Early Childhood, 2018)
This article analyses the status of early childhood education in Pakistan. The education systems in place in Pakistan are mainly framed within a didactic approach to teaching and learning, which addresses certain areas of education but does not teach the child as a whole. Domains of children’s holistic development such as social, ethical, cultural, intellectual, emotional and physical well-being, and some other key academic skills, are not fully covered. In this kind of education, students are taught to follow rules without question and do as instructed, which corresponds to an autocratic view of learning. In the context of early childhood education in Pakistan, teachers occupy dominant roles, which positions them as the imparters and sources of knowledge and children as dependent and the receivers of knowledge, rather than considering them as potential, curious and powerful learners with unlimited capabilities. The literature indicates that this approach to teaching and learning does not privilege the holistic development and well-being of children. In contrast, many developed countries use research-based contemporary approaches to children’s education and development, giving children a more central role in their learning to ensure that every child has the opportunity to develop to their full potential. This kind of approach reminds teachers to view all children not as needy or deficient individuals.
KerkoCite.ItemAlsoKnownAs: 10.1177/1463949118757049 2339240:EGKJGMSG 2405685:CTRU98H8

The Importance of Educating Girls in the Newly Merged Districts of Khyber Pakhtunkhwa, Pakistan: Policy Paper - Naveed, Sumbal (Center for Universal Education at The Brookings Institution, 2018)
The Federally Administered Tribal Areas (FATA) in Pakistan, named the Newly Merged Districts (NMDs) of Khyber Pakhtunkhwa province in July 2018, have begun rebuilding after years of Talibanization and military operations. This policy paper focuses on how the government-led education activities can be best aligned to make education possible for the districts' girls, who have long been excluded from education due to conflict and war. Based on stakeholder perceptions, the paper identifies some barriers missed by the FATA's Education Sector Plan (ESP) and points out the opportunities within communities to accelerate the efforts to improve the girls' participation in schools. The results of the study propose to use a gender lens for planning and implementing the activities that can improve access to quality education, to prepare the girls for a better and more productive life.
Publication Title: Center for Universal Education at The Brookings Institution KerkoCite.ItemAlsoKnownAs: 2339240:PD3LB7X3 2405685:L554ELH5
Keywords: Access to Education; Attitude Change; Barriers; Community Involvement; Cultural Influences; Educational Finance; Educational Planning; Educational Quality; Equal Education; Equal Opportunities (Jobs); Females; Foreign Countries; Gender Bias; Governance; Government Role; Males; Political Issues; Single Sex Schools; Social Attitudes; Teacher Competencies; Transportation; War; Women Faculty

"Shall I feed my daughter, or educate her?": barriers to girls' education in Pakistan - Martínez, Elin; Human Rights Watch (Human Rights Watch, 2018)
"This report concludes that many girls simply have no access to education, including because of a shortage of government schools - especially for girls. Nearly 22.5 million of Pakistan's children - in a country with a population of just over 200 million - are out of school, the majority of them girls. Thirty-two percent of primary school age girls are out of school in Pakistan, compared with 21 percent of boys. By ninth grade, only 13 percent of girls are still in school."–Publisher website
OCLC: on1080863817 KerkoCite.ItemAlsoKnownAs: 2339240:VAUXG7LJ 2405685:QVL4MLZF 2405685:TIVVZGFN
Keywords: Education; Girls; Pakistan; Schools; Sex discrimination in education; Social conditions; auto_merged

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode